Protein supplementation elicits greater gains in maximal oxygen uptake capacity and stimulates lean mass accretion during prolonged endurance training: a double-blind randomized controlled trial. Issue 2 (26th June 2019) - Knuiman, Pim; van Loon, Luc J C; Wouters, Jeroen; Hopman, Maria; Mensink, Marco
ABSTRACT: Background: Endurance training induces numerous cardiovascular and skeletal muscle adaptations, thereby increasing maximal oxygen uptake capacity (VO2max ). Whether protein supplementation enhances these adaptations remains unclear. Objective: The present study was designed to determine the impact of protein supplementation on changes in VO2max during prolonged endurance training. Methods: We used a double-blind randomized controlled trial with repeated measures among 44 recreationally active, young males. Subjects performed 3 endurance training sessions per week for 10 wk. Supplements were provided immediately after each exercise session and daily before sleep, providing either protein (PRO group; n = 19; 21.5 ± 0.4 y) or an isocaloric amount of carbohydrate as control (CON group; n = 21; 22.5 ± 0.5 y). The VO2max, simulated 10-km time trial performance, and body composition (dual-energy X-ray absorptiometry) were measured before and after 5 and 10 wk of endurance training. Fasting skeletal muscle tissue samples were taken before and after 5 and 10 wk to measure skeletal muscle oxidative capacity, and fasting blood samples were taken every 2 wk to measure hematological factors. Results: VO2max increased to a greater extent in the PRO group than in the CON group after 5 wk (from 49.9 ± 0.8 to 54.9 ± 1.1 vs 50.8 ± 0.9 to 53.0 ± 1.1 mL · kg −1 · min −1 ; P < 0.05) and 10 wk (from 49.9 ± 0.8 to 55.4 ± 0.9 vs 50.8 ± 0.9 to 53.9 ± 1.2 mL · kg −1 · min −1 ; P < 0.05). Lean body mass increased in the PRO group whereas lean body mass in the CON group remained stable during the first 5 wk (1.5 ± 0.2 vs 0.1 ± 0.3 kg; P < 0.05) and after 10 wk (1.5 ± 0.3 vs 0.4 ± 0.3 kg; P < 0.05). Throughout the intervention, fat mass reduced significantly in the PRO group and there were no changes in the CON group after 5 wk (−0.6 ± 0.2 vs −0.1 ± 0.2 kg; P > 0.05) and 10 wk (−1.2 ± 0.4 vs −0.2 ± 0.2 kg; P < 0.05). Conclusions: Protein supplementation elicited greater gains in VO2max and stimulated lean mass accretion but did not improve skeletal muscle oxidative capacity and endurance performance during 10 wk of endurance training in healthy, young males. This trial was registered at clinicaltrials.gov as NCT03462381.